EXHUMATION -A KEY TO PROVIDE JUSTICE TO VICTIMS OF HOMICIDE: SITUATION IN LARKANA AND SUKKUR DIVISIONS - Humayun, Muhammad; Khichi, Zawar Hussain; Chand, Haresh; Khan, Omair; ullah, Asad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Foul play in cases of hurt and homicide is an established fact. People on basis of enmity falsely charge their enemies; this practice is carried out globally. The purpose of present study was to know the situation in the study area and also to know the risk factors which make hindrance in providing justice in exhumed cases. Methods: The present study was conducted over a period of 3 and half years from Jul 2006 to Dec 2009. During the said period total 21 exhumations were carried out in Sukkur and Larkana Divisions by the team of Chandka Medical College, Larkana. Cases were studied in Forensic Medicine Department of Chandka Medical College, Larkana. Out of 21 cases, only 9 cases were positive (autopsy). In rest of 12 cases, autopsy reports remained undetermined due to advanced decomposition/putrefaction of corpses. Results: During the study period, total 21 exhumations (autopsies) were carried out in different districts of Larkana and Sukkur divisions. There were 17 male cases and 4 female cases. Cases were divided in to 4 groups on age basis. Group-1 from 0-5 years, Group-2 from 16-30 years, Group-3 from 31-45 years, Group-4 from 46-65 years. The maximum number of cases fall in group-2 which are 15 (71.42%) and minimum in group-1 which is 1 (4.76%). Out of 21 cases, only in 9 cases cause of death was ascertained and majority of these were firearm injuries (5, 55.55%), two (22.22%) cases of drowning, one (11.11%) strangulation and one blunt trauma. The success rate remained 42.85%. Nineteen cases were of primary autopsy (First time) on exhumation and 2 cases were secondary (re-examination). Conclusion: The success rate in challenge cases depends mostly on the duration of exhumation and soil of cemetery. If a foul play is suspected then there should be no unnecessary delay in conduction of exhumation. If exhumation is carried out within days after burial, 90% results can be achieved. Keywords: Exhumation, Justice, Victims, Homicide